Maritime Connections between New Zealand and Sri Lanka: Connected by Empire, Separated by Distance - Senaratne B; Nicklin G (Centre for Defence and Security Studies, Massey University)
Smaller states do not receive the same attention as larger powers when discussing maritime security. Island-states are worthy of attention because of their sizeable, large maritime zones. New Zealand and Sri Lanka are such islands with significant maritime security interests and responsibilities, located adjacent to larger powers. They warrant an examination even though their geographical locations generate different maritime security dynamics and are vastly different in their land mass. Unfortunately, there is a dearth of literature pertaining to the bilateral relations. This highlights that there has been minimal emphasis on New Zealand-Sri Lanka bilateral relations even from an academic perspective. Therefore, we examine why New Zealand and Sri Lanka, which were intricately connected through the British Empire did not continue to maintain ties with one another, regardless of similarities between the two states. While distance and lack of awareness of the similarities have resulted in distanced relations, we argue that there is much to learn about smaller island-states from comparing our respective maritime interests.
Keywords: British Empire; Island-state; Maritime Security; Maritime Connections; New Zealand; Sri Lanka